Customer versus member engagement: Does mutuality matter?. Issue 1 (June 2022) - Mazzarol, Tim; Soutar, Geoffrey N.; Reboud, Sophie; Clark, Delwyn
Abstract: The purpose of this study was to examine the relative importance of customer engagement (CE) on customer loyalty (CL) and word of mouth (WOM) within co-operative and mutual enterprises (CMEs), and to see how these relationships compared to those found in more mainstream investor-owned businesses (IOFs). A large sample (n = 856) of CME members and IOF customers was drawn from an online consumer panel, with broadly equal numbers in each, who completed a questionnaire examining their CE, CL, and propensity for WOM. A path model, estimated by PLS, was used to examine the relationships between four dimensions of CE (engagement attention, co-development, enthusiasm, and interaction). Although the study did not find significant differences between CME members and IOF customers in terms of the influence CE had on CL and WOM, it did find CME members had higher CE scores across all dimensions. With engagement enthusiasm (EE) as the most influential factor, followed by engagement attention (EA). The study provides empirical evidence of the influence CE has on both CL and WOM, as well as the propensity of CME members to have higher levels of CE. This offers robust support to the importance of mutuality within CME businesses. The study provides further evidence of the importance of CE in fostering CL and WOM, as well as the relative importance of EE enthusiasm and EA in this. For managers of CMEs the study shows the strength of mutuality in fostering member CE. For IOF managers, it suggests that CE does matter, and it should be monitored. Highlights: Engagement attention and engagement enthusiasm have most influence on loyalty and WOM. CME members were significantly more engaged across all factors than were customers of investor-owned firms (IOFs). No significant differences were found between CME members and IOF customers in their loyalty or WOM activity. CMEs have a natural advantage in member engagement, but don't take advantage of this in their competition with IOFs.